A pilot study of novel duodenal covered self-expandable metal stent fixation - Yasuki Hori (Nature Portfolio, 2021)
Abstract Migration of duodenal covered self-expandable metal stents (C-SEMSs) is the main cause of stent dysfunction in patients with malignant gastric outlet obstruction (mGOO). Because endoscopic SEMS placement is frequently selected in patients with poor performance status, we concurrently focused on the safety of the treatment. This pilot study included 15 consecutive patients with mGOO who underwent duodenal partially covered SEMS (PC-SEMS) placement with fixation using an over-the-scope-clip (OTSC). Technical feasibility, clinical success for oral intake estimated by the Gastric Outlet Obstruction Scoring System (GOOSS) score, and adverse events including stent migration were retrospectively assessed. All procedures were successful, and clinical success was achieved in 86.7% (13/15). Mean GOOSS scores were improved from 0.07 to 2.53 after the procedure (P < 0.001). Median survival time was 84 days, and all patients were followed up until death. Stent migration occurred in one case (6.7%) at day 17, which was successfully treated by removal of the migrated PC-SEMS using an enteroscope. For fixation using an OTSC, additional time required for the procedure was 8.9 ± 4.1 min and we did not observe OTSC-associated adverse events. Poor performance status was associated with clinical success (P = 0.03), but we could provide the treatment safely and reduce mGOO symptoms even in patients with poor performance status. In conclusion, duodenal PC-SEMS fixation using an OTSC is feasible for preventing stent migration in patients with mGOO including those with poor performance status.